Paying Them to Hate US: The Effect of U.S. Military Aid on Anti-American Terrorism, 1968-2014 - Eugen Dimant; Tim Krieger; Daniel Meierrieks (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Does U.S. military aid make the United States safer? To answer this question, we collect data on 173 countries between 1968 and 2014. Exploiting quasi-random variation in the global patterns of U.S. military aid, our paper is the first to provide causal estimates of the effect of U.S. military aid on anti-American terrorism. We find that higher levels of military aid led to an increased likelihood of the recipient country to produce anti-American terrorism. For our preferred instrumental-variable specification, doubling U.S. military aid increases the risk of anti-American terrorism by 4.4 percentage points. Examining potential transmission channels, we find that more U.S. military aid leads to more corruption and exclusionary policies in recipient countries. Consistent with a theoretical argument developed in this paper, these results indicate that the inflow of military aid induces rent-seeking behavior, which in turn encourages terrorism by groups that suffer from reduced economic and political participation as a consequence of rent-seeking. These groups direct their dissatisfaction against the United States as the perceived linchpin of an unfavorable status quo in the recipient country.
Keywords: D74; F35; 330; U.S. military aid; anti-American terrorism; transnational terrorism; instrumental variable estimation